KINERJA KUALITAS PELAYANAN KORPORASI PANGAN PETANI (KPP) PROVINSI JAWA BARAT - Riantin Hikmah Widi; Tuti Karyani; Hepi Hapsari; Lucyana Trimo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
The Farmer's Food Corporation (KPP) as a corporate entity needs to make efforts to survive and be sustainable. This research was conducted on 196 farmers as members of KPP West Java. The purpose of this study was to analyze the performance of KPP service quality in West Java Province. The methodology used in this research is a survey with sampling through Multistage Cluster Random Sampling. The performance of the service quality of the Farmer's Food Corporation (KPP) was analyzed using descriptive statistical analysis. The results of this research are the service quality of the Farmer's Food Corporation (KPP) using the approach of reliability (reliability), responsiveness (responsiveness), assurance (guarantee), tangibles (direct evidence), and empathy (empathy). The reliability subsystem is the performance with the highest gain, namely the ability of KPP to provide services as promised accurately and reliably. tangibles (direct evidence) obtained high performance in service quality at the Farmer's Food Corporation, but implementation was still difficult to do, because farmers often made purchases of production facilities to agricultural shops. Overall, the quality of services provided by the corporation to farmers is in the high category.